2006
DOI: 10.1111/j.1442-2050.2006.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and clinical course of patients with hypopharyngeal carcinoma

Abstract: In the period between 1 January 1978 and 1 January 2004, 85 patients with hypopharyngeal squamocellular carcinoma were admitted at the Department of Esophagogastric Surgery in Belgrade. Among them, only 46 patients (54.1%) had radical surgical en-block resection and functional neck dissection, and they were included into an historical cohort study. In 40 patients a pharyngolaryngoesophagectomy was performed using for reconstruction, stomach tissue in 29 and colon tissue in 11 patients. Since 1996, in six patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
0
37
0
6
Order By: Relevance
“…According to the published data total morbidity is between 30-60% [10,12,[22][23][24][25]. The morbidity rate was 46.2% in our series.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…According to the published data total morbidity is between 30-60% [10,12,[22][23][24][25]. The morbidity rate was 46.2% in our series.…”
Section: Discussionmentioning
confidence: 77%
“…It is reported that estimation of synchronous or metachronous malignancy in such tumors is between 10-60% [10,15,[19][20][21]. The presence of synchronous malignancy in these tumors and the multicentricity should be evaluated with advanced radiologic and endoscopic procedures preoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations